2021
DOI: 10.1016/j.omto.2021.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Activation of interferon regulatory factor 3 by replication-competent vaccinia viruses improves antitumor efficacy mediated by T cell responses

Abstract: Recently, oncolytic vaccinia viruses (VACVs) have shown their potential to provide for clinically effective cancer treatments. The reason for this clinical usefulness is not only the direct destruction of infected cancer cells but also activation of immune responses directed against tumor antigens. For eliciting a robust antitumor immunity, a dominant T helper 1 (Th1) cell differentiation of the response is preferred, and such polarization can be achieved by activating the Toll-like receptor 3 (TLR3)-interfero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Tumor volume ( b , d ) and overall survival ( c , e ) are plotted for 9–14 mice per group +SEM. Data shown in ( b ) for the control groups PBS and WR/TK– is the same as published in [ 23 ] as both studies were done in the same experiment following the principle of the 3Rs. * p < 0.05; ** p < 0.01, *** p < 0.001.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tumor volume ( b , d ) and overall survival ( c , e ) are plotted for 9–14 mice per group +SEM. Data shown in ( b ) for the control groups PBS and WR/TK– is the same as published in [ 23 ] as both studies were done in the same experiment following the principle of the 3Rs. * p < 0.05; ** p < 0.01, *** p < 0.001.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, A46 binds and inhibits TRIF [ 36 ], B19 is a soluble type I interferon receptor [ 37 ], and K7 binds DDX3 [ 38 ]. Previously, we attempted to activate the IRF3 pathway by deleting several of these proteins [ 23 ]. We demonstrated that combining a deleted thymidine kinase gene with truncations in immunomodulatory proteins C6 (interacts with NAP1, TANK, and SINTBAD [ 39 ]), N2 (blocks nuclear translocation of P-IRF3 [ 40 ]), or C10 (prevents dsDNA recognition by DNA-PK [ 41 ]) did not translate into IRF3 phosphorylation after cell infection; these three deletions needed to be combined in one virus (named WR/TK-/3Δ) in order detect IRF3 activation and subsequent type I interferon expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetically engineered Sendai Virus carrying the IL-2 gene stimulates antitumor effects by modulating immune cell populations [88]. Oncolytic vaccinia viruses, armed with immunomodulatory molecules play a crucial role in activating molecular immune responses against cancer [89][90][91][92][93][94][95][96][97][98]. These viruses enhance antitumor efficacy by stimulating the activation of CD4+ and CD8+ T cells, promoting immune cell infiltration, and augmenting immune-based antitumoral activity through the delivery of chemokines and immunomodulatory antibodies.…”
Section: Engineering Viruses To Trigger Immune Signalingmentioning
confidence: 99%
“…A recent study demonstrated that deleting three key immune-evasion gene products (C10L, N2L, and C6L) from VACV preserved its replication ability in cancer cells [30]. Proteins encoded by VACV, including C10, A46, N2L, and C6, acted as antagonists in the TLR3-IRF3 signaling pathway in various stages [31].…”
Section: Deletion Of Immune-evasion Genes In Vacv To Enhance Tumor Se...mentioning
confidence: 99%